2010
DOI: 10.1007/s00412-010-0300-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 trimethylation at lysine 9 marks the inactive metaphase X chromosome in the marsupial Monodelphis domestica

Abstract: In somatic cells of female marsupial and eutherian mammals, X chromosome inactivation (XCI) occurs. XCI results in the transcriptional silencing of one of the two X chromosomes and is accompanied by specific covalent histone modifications attributable to the inactive chromatin state. Because data about repressed chromatin of the inactive X chromosome (Xi) in marsupials are sparse, we examined in more detail the distribution of active and inactive chromatin markers on metaphase X chromosomes of an American mars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Some modifications were completely absent from the marsupial Xi (Koina et al, 2009;Chaumeil et al, 2011), whereas others were restricted to specific windows of the cell cycle (Chaumeil et al, 2011). Of considerable surprise was the accumulation of marks on Xi that are associated with pericentromeric heterochromatin (Mahadevaiah et al, 2009;Rens et al, 2010;Chaumeil et al, 2011;Zakharova et al, 2011). Thus, it seems that the marsupial Xi bears an epigenetic signature similar to that of pericentromeric heterochromatin, and is unlike the XIST-associated facultative heterochromatin in eutherians.…”
Section: Marsupial XCImentioning
confidence: 99%
“…Some modifications were completely absent from the marsupial Xi (Koina et al, 2009;Chaumeil et al, 2011), whereas others were restricted to specific windows of the cell cycle (Chaumeil et al, 2011). Of considerable surprise was the accumulation of marks on Xi that are associated with pericentromeric heterochromatin (Mahadevaiah et al, 2009;Rens et al, 2010;Chaumeil et al, 2011;Zakharova et al, 2011). Thus, it seems that the marsupial Xi bears an epigenetic signature similar to that of pericentromeric heterochromatin, and is unlike the XIST-associated facultative heterochromatin in eutherians.…”
Section: Marsupial XCImentioning
confidence: 99%
“…Based on the accumulation of H3K27me3 on the marsupial inactive X-chromosome, it was proposed that imprinted X-inactivation may have a common mechanism with marsupials and placental mammals (Mahadevaiah et al 2009). However, subsequent studies revealed that trimethylation at H3K9 (H3K9me3) and HP1 are stable markers of marsupial inactive X-chromosomes and that H3K27me3 accumulation is transient and labile (Chaumeil et al 2011; Rens et al 2010; Zakharova et al 2011). H3K9me3 and HP1 are well-characterized markers of pericentromeric heterochromatin and are also conserved markers of mammalian PMSC in spermiogenesis (Namekawa et al 2007), supporting a notion that germline silencing is the ancestral driving force of imprinted X-inactivation in the absence of Xist RNA in marsupials.…”
Section: X-chromosome Inactivation In Germ Cells and Pre-implantationmentioning
confidence: 99%
“…S8). This alternating pattern was previously found on the inactive X chromosome of other placental mammals and seems to reflect two different types of facultative heterochromatin acting in XCI [15,16,[38][39][40][41]. However, no H3K9me3 enrichment (excluding the centromeric region) was detected on the inactive X chromosome in the female rEFs used for the NF13 line generation.…”
Section: Fig 4 Monolayer Differentiation Of Rat Pluripotent Cells Omentioning
confidence: 59%
“…5B-D and Supplementary Fig.S8). Using a combination of IF, RNA, and DNA FISH, we tested X chromosomes for loss of active chromatin marks and enrichment of repressive histone modifications that had been found on the inactive X chromosome in other mammals [15,16,[38][39][40][41]. In all the three cell lines, shortly after Xist RNA coating, X chromosome undergoing XCI was depleted in H3K4me2, an active chromatin marker, and enriched with H3K27me3 and ubiquitylated H2A (uH2A), repressive chromatin modifications.…”
Section: Fig 4 Monolayer Differentiation Of Rat Pluripotent Cells Omentioning
confidence: 99%